The Role of Public Health Awareness in Disease Prevention: A Critical Analysis - Ibrahim Mohammed Nasser Khubrani; Sultan Abdullah Mohammed Alshehri; Khalid Ali Ahmed Mathwi; Ahmed Ali Mofareh Algharamah; Teef Salem Al-Anzi; Mohammed Hassan Asiri; Thamer Mohammed Hamoud Halawani (The Bioscan, 2025)
Public health awareness plays a pivotal role in disease prevention by empowering individuals and communities with knowledge and resources to adopt healthier behaviors. This article critically analyzes the impact of public health awareness initiatives on preventing both communicable and non-communicable diseases. Drawing on case studies and existing literature, the analysis highlights successful campaigns, identifies challenges such as misinformation and cultural barriers, and explores the role of stakeholders, including governments, healthcare providers, and media. Recommendations are provided to enhance the effectiveness of future awareness campaigns through evidence-based strategies and inclusive approaches. The article underscores the need for sustained efforts to bridge gaps in awareness and foster global health equity.